PRECOMPETITION ANXIETY AND STRESS IN TENNIS: REVIEW OF LITERATURE - Vasilios Koronas; Dragos Ioan Tohanean; Konstantinos SALONIKIDIS (Editura Universitatii Transilvania din Brasov, 2020)
The purpose of this project is to examine the impact of competitive stress on tennis athletes and propose solutions for controlling and treating it. Pre-competition stress is a negative feeling for an athlete, which most often comes from expecting a victory. In the present work a general reference is made initially to human stress, which is caused by a variety of factors, whether specific or not, afflicting a large part of the population. Then follows an introduction to the basic features of precompetition anxiety, followed by an observation on the psychological stressrelief skills and how they can be applied. In conclusion, the overcome of the stressful situations depends on maintaining focus of predefined goals, gaining competitive experience and preserve emotional balance during the process.